Northwest history. Mining. Exploration. 1920-06-11 (1920)
To reach ledge by new crosscut - WIlliam Schierding of Spokane manager of the Friend Mining company, says a crusscut is to be started at once from the bottom of the 60 foot shaft to reach the ledge, which he estimates is about 10 feet away. The property is on Beaver creek in the Coeur d'Alenes.